Calculation of Inversion Time (TI) value for Fat suppression in the modified Spin Echo sequence method. - Kalagi, Sunil (British Journal of Healthcare and Medical Research, 2018)
Fat suppression is commonly used in Magnetic Resonance Imaging (MRI) to suppress the signal from adipose tissue or detect adipose tissue. Due to short relaxation times, fat has a high signal on magnetic resonance images (MRI). This high signal, easily recognized on MRI. The high signal due to fat may be responsible for artifacts such as ghosting and chemical shift. Lastly, a contrast enhancing tumor may be hidden by the surrounding fat. These problems have prompted development of fat suppression techniques. in MRI. Fat may be suppressed on the basis of its difference in resonance frequency with water by means of frequency selective pulses or phase contrast techniques, or on the basis of its short TI relaxation time by means of inversion recovery sequences. The aim of this paper is to study the Fat suppression technique using Inversion recovery Pulse sequence by calculating TInull parameter for the pulse sequence.